The sacred and the everyday: exploring the relationship between religious space and public - Chogle, Shafeea (School of Architecture, Planning and Geomatics, 2018)
This dissertation began with an interest in the relationship between religious space and the public realm, and a curiosity into the capacity of religious spaces to participate in and construct public. This interest, while conscious of global ideas surrounding the role of religion in the global south, is strongly rooted in the emerging urban conditions of the Delft settlement in Cape Town. Where historically the secular and the sacred have been separated along the same lines as the physical and spiritual, rational and irrational, modern and traditional, public and private (Gravelling, 2010: 198); this dissertation maintains to move beyond these separations and instead explore the overlaps, connections, and mediations, in a context where religious entities are actively taking hold of the spaces the secular has failed to fill. In this context, characterised by poor quality environments, high densities, and weak institutional presence, religious space has emerged into the public realm, thus becoming the intersection of public and private, of visible and invisible worlds. The project therefore departs from the position that religious space is a material asset capable of advancing social capital, facilitating networks, offering refuge, and providing a platform for the social and public life of a community.